Endothelial vasodilation after a high-volume training load and tapered training in collegiate female swimmers - Weihl, F. M.; Van Guilder, G. P. (The Journal of Strength and Conditioning Research, 2021)
High-volume endurance training loads have been linked to adverse remodeling of the heart and large arteries; yet, data on the vascular endothelial function are unclear. Moreover, although collegiate-level endurance athletes often perform high-volumes of vigorous endurance training and resistance training as part of their strength and conditioning programs, it is unknown whether they also experience vascular abnormalities, particularly changes in endothelial function. The aim of this study was to verify the impact of a high-volume training load phase followed by low-volume tapered training on endothelial vasodilator function in National Collegiate Athletic Association (NCAA) Division I competitive female swimmers. Microvascular endothelial vasodilation was assessed by pulse arterial tonometry that provides a reactive hyperemia index in 10 female NCAA Division 1 swimmers after 4 weeks of a high-volume training load, and subsequently, after 3 weeks of low-volume tapered training as part of preparation for annual conference championships. The reactive hyperemia index was calculated as the ratio of the pulse volume amplitude after 5 minutes of left-arm brachial artery ischemia to the baseline amplitude, divided by same ratio in the contralateral arm. The high-volume training load included a 4-week block of dual-day sessions (120 minutes per practice) consisting of vigorous intensity endurance and high-intensity interval/sprint swim training, coupled with 5K running, resistance training, and Olympic weightlifting. Tapered training consisted of 3 weeks of 3-5 swims per week at ~50% VO2max for 60 minutes per practice (~4,000 minutes per practice). The reactive hyperemia index (1.73 ± 0.50) was low in athletes after the high-volume training load with 8 athletes demonstrating endothelial dysfunction. However, after tapered training, the reactive hyperemia index was ~33% higher (2.29 ± 0.43; 95% confidence interval [CI]: 1.98-2.60, p = 0.0223 vs. the high-volume training load). Effect size, as expressed by the partial eta2 (0.46) and Cohen's dz (1.1923; 95% CI: 0.1687-2.4643) with tapered training, was large. These results demonstrate distinct differences in endothelial vasodilation after 4 weeks of a high-volume training load compared with a 3-week taper in NCAA Division I female swimmers.